Mixed metal oxide: a new class of catalyst for methanol activation - Mehta, Shweta; Agarwal, Sheena; Kenge, Nivedita; Mekala, Siva Prasad; Patil, Vipul; Raja, T.; Joshi, Kavita (Applied Surface Science, 2020)
In this work, we propose a mixed metal oxide as a catalyst and demonstrate it's ability to not only activate the MeOH molecule upon adsorption but also dissociate O-H and one of it's C-H bonds. MeOH activation is compared on two prominent facets of ZnAl(2)O(4 )viz. (2 2 0) and (31 1). While spontaneous O-H bond dissociation is observed on both facets, C-H bond dissociates only on the (3 1 1) surface. Multiple factors like atomic arrangement and steps on the surface, coordination of surface atoms, and their effective charges have a combined effect on MeOH activation. The (3 1 1) surface offers higher catalytic activity in comparison with (2 2 0) surface. Having a stepped surface, availability of multiple sites, and variation in the charge distribution are some of the reasons for better catalytic performance of (3 1 1) facet. Effect of orientation of MeOH with respect to the surface adds both, information and complexity to the problem. Observations pertinent to understanding this effect are also reported. A detailed analysis of atomic arrangement on the two surfaces provides a rationale as to why MeOH gets dissociated spontaneously on the mixed metal oxide. The promising results reported here opens up a new class of catalyst for research.
Keywords: DFT; MeOH; Spontaneous dissociation; ZnAl2O4

Aqueous methanol to formaldehyde and hydrogen on Pd/TiO2 by photocatalysis in direct sunlight: structure dependent activity of nano-Pd and atomic Pt-coated counterparts - Nalajala, Naresh; Salgaonkar, Kranti N.; Chauhan, Inderjeet; Mekala, Siva Prasad; Gopinath, Chinnakonda S. (ACS Applied Energy Materials, 2021)
In the present investigation, facet-controlled Pd nanoparticles with nanocube (Pd-NC) and truncated octahedron (Pd-TO) morphologies, and their counterparts with half-a-monolayer of atomic Pt coated (0.5 theta(Pt)-Pd-NC and 0.5 theta(Pt)-Pd-TO) surfaces were prepared. All of them were characterized and evaluated as cocatalyst after supporting them on commercial titania (P25) (Pd-NC/P25, Pd-TO/P25, 0.5 theta(Pt)-Pd-NC/P25, and 0.5 theta(Pt)-Pd-TO/P25) under direct sunlight and/or one sun conditions for the oxidation of methanol to formaldehyde along with solar hydrogen production. Pd-NC/P25 shows higher activity for hydrogen generation compared to Pd-TO/P25; however, activity reversal occurs with the above cocatalysts, but, after Pt-coating with further enhanced activity. The highest conversion of methanol (0.2 mu mol/h.mg) to 100% selective formaldehyde was observed with 0.5 theta(Pt)-Pd-TO/P25, while other catalysts show significantly lower methanol conversion in the following order: 0.5 theta(Pt)-Pd-TO/P25 > 0.5 theta(Pt)-Pd-NC/P25 > Pd-NC/P25 > Pd-TO/P25. Pt-coated on (111) facets of Pd-TO simulates the activity associated as that of Pt(111) facets and demonstrating the highest and facet dependent activity. The present study is truly in resonance with exploiting the surface properties for heterogeneous catalysis, and highlights that less than a monolayer of Pt is sufficient to simulate the activity as that of bulk Pt. It is worth exploring this concept to other metals and substrates too.
Keywords: heterogeneous catalysis; Nanomaterials; Oxidation; Photocatalysis; surface modification

Green synthesis of cyclohexanone to adipic acid over Fe-W oxides incorporated mesoporous carbon support - Mekala, Siva Prasad; Prabu, Marimuthu; Gawali, Sheetal Datta; Gopakumar, Karthik; Gogoi, Pranjal; Bhatkar, Akash Ravindra; Mohapatra, Gourab; Unnikrishanan, Eeswar; Raja, Thirumalaiswamy (Catalysis Communications, 2022)
We have prepared iron and tungsten oxides incorporated mesoporous carbon (MC) catalysts using a simple hydrothermal methodology with different carbon sources, and the catalytic performance was investigated for cyclohexanone oxidation. An adequate amount of metal oxide loading has displayed a key role in the selective catalyst for adipic acid (AA) synthesis. The MC catalyst has shown its prime activity under the influence of redox properties of W5+/W6+ and Fe2+/Fe3+ as promoters. The 10%Fe 90%W-MC fructose as a carbon source catalyst has provided its best selectivity of 87% for AA at 120 ?C.
Keywords: Adipic Acid; Liquid phase oxidation; mesoporous carbon; Redox center

Microwave-assisted selective N-alkylation of aniline over molybdenum supported catalyst - Bhatkar, Akash; Mane, Samruddhi; Mekala, Siva Prasad; Gogoi, Pranjal; Mohapatra, Gourab; Ramakrishnan, Archana; Marimuthu, Prabu; Thirumalaiswamy, Raja (Catalysis Communications, 2022)
Selective N-alkylation of aniline is a tough and challenging reaction due to over alkylation, therefore, catalyst with specific characteristics is needed to accomplish such transformations. In this work, a series of catalysts with molybdenum supported on alumina are prepared and subjected to various reaction conditions, out of which 30 PMA (Phosphomolybdic acid) showed the best result due to its proper combination of acidic sites. This reaction is sustainable and environmentally friendly as it is carried out with methanol as an alkylating source in the presence of microwave radiation at low temperature. The reaction data was compared with various other reactor systems too.

MnXWO4 nanostructure-based catalysts for single-step oxidation of cyclohexane and methane to oxygenates - Prabu, Marimuthu; Manikandan, Marimuthu; Samal, Pragnya Paramita; Gurrala, Lakshmi Prasad; Mekala, Siva Prasad; Archana, Ramakrishnan; Nayak, Chandrani; Bhattacharyya, D.; Jha, S. N.; Krishnamurty, Sailaja; Raja, Thirumalaiswamy (ACS Applied Nano Materials, 2023)
Activation of the C-H bond in cyclohexane (CYH) and methane is a crucial step to obtain desirable oxygenated products using nanostructured catalyst and is a great challenge and an efficient route to mitigate the inauspicious effects of climate change. The active sites were identified using XRD, HR-TEM, SEM, N2 sorption analysis, TPR, Raman, XPS, TGA, in situ DRIFT, XAS, etc. In optimal reaction conditions, 46% of CYH was converted into adipic acid (AA) on MnxWO4 nanostructures within 6 h. The recyclability test confirmed the catalyst heterogeneity, which revealed no appreciable loss of catalytic activity even after three consecutive reactions. In situ DRIFT study reveals that CYH is oxidized to cyclohexanone and cyclohexanol (KA oil) and is further oxidized to AA via carboxylate intermediates. DFT studies disclosed that MnOx species are responsible for the C-H activation of CYH, and the Mn2+/Mn3+ redox centers play a vital role in the absorption of KA oil to form AA. Herein, we demonstrated the significant role of the ``MnOx'' species and that adequate Lewis and Bronsted acidic sites, redox centers of (Mn2+/Mn3+), and lattice oxygen are accountable for the CYH conversion toward the AA. Additionally, we have reported the oxidation of methane to methanol (146 mu mole per gram of catalyst) in the presence of water at 75 degrees C without over-oxidation products.
Keywords: Adipic Acid; C-H bond activation; Cyclohexane oxidation; methane activation; MnOx chain; Redox center

New insights into the composition and catalytic performance of VOx-Ga/γ-Al2O3 for the oxidative dehydrogenation of propane to propene - Kandasamy, Prabu; Gawali, Sheetal; Venugopalan, Aswathy Thareparambil; Manikandan, Marimuthu; Mekala, Siva Prasad; Shelke, Ankita; Ajithkumar, Thalasseril G.; Bhatte, Kushal; Raja, Thirumalaiswamy (New Journal of Chemistry, 2024)
Oxidative dehydrogenation (ODH) of propane is a promising alternative route for propene production. In this work, we developed a series of vanadium and gallium oxides supported on gamma-Al2O3 catalysts by an incipient wetness impregnation method. Among the employed catalysts, the VGA-2 showed superior catalytic activity, and the catalyst was demonstrated for longevity in ODH of propane with a stable activity using a continuous flow fixed bed reactor at 400 degrees C. H-2-TPR and UV-visible spectra showed the presence of highly dispersed monomeric VOx species with tetrahedral coordination geometry, which influences product selectivity. The characterization results also conferred that the redox nature of vanadium (V5+ and V4+) oxide and higher V5+ content on the surface of the VGA-2 catalysts are more favourable for C-H activation. In addition, the pyridine-FTIR and Ga-71 solid-state NMR studies further substantiated the presence of Lewis acid sites and tetrahedrally coordinated Ga3+Ox species that are highly responsible for the ODHP activity, respectively. Furthermore, in situ-DRIFTS studies conferred that the propane adsorption at ambient temperature showed the formation of intermediate propoxide species with the evolution of sigma-bonds and with further increase in the temperature to 325 degrees C; the stretching vibrations of the =C-H and -C-H bonds in the propylene molecule were observed. The spent catalysts were also analyzed by thermogravimetric analysis, where the optimized catalyst (VGA-2) showed the least coke deposition.